2014
DOI: 10.3892/mmr.2014.2735
|View full text |Cite
|
Sign up to set email alerts
|

Octreotide attenuates liver fibrosis by inhibiting hepatic heme oxygenase-1 expression

Abstract: The aim of the present study was to investigate the effects of octreotide treatment on hepatic heme oxygenase-1 (HO-1) expression, together with the influence of altered hepatic HO-1 expression levels on hepatic function and fibrosis in bile duct-ligated rats. The rats were divided randomly into sham, cirrhotic, cobalt protoporphyrin and octreotide treatment groups. The expression levels of hepatic HO-1 mRNA were measured by reverse-transcription polymerase chain reaction, while the protein expression was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
(46 reference statements)
2
6
0
Order By: Relevance
“…Indeed, HO-1 overexpression significantly exacerbates liver fibrosis and portal hypertension induced by chronic BDL in rats. 25 , 33 , 34 Further, and in agreement with our results, chronic HO-1 overexpression directly promotes hepatic iron accumulation in BDL rats, 25 , 37 whereas iron chelation diminishes liver fibrosis. 37 We found that RIP3 −/− primary hepatocytes displayed increased iron levels compared with WT hepatocytes, being iron content modulated by HO-1 activity.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Indeed, HO-1 overexpression significantly exacerbates liver fibrosis and portal hypertension induced by chronic BDL in rats. 25 , 33 , 34 Further, and in agreement with our results, chronic HO-1 overexpression directly promotes hepatic iron accumulation in BDL rats, 25 , 37 whereas iron chelation diminishes liver fibrosis. 37 We found that RIP3 −/− primary hepatocytes displayed increased iron levels compared with WT hepatocytes, being iron content modulated by HO-1 activity.…”
Section: Discussionsupporting
confidence: 91%
“…HO-1 is a well-established stress-inducible enzyme, 32 found upregulated in the liver of BDL rats. 25 , 33 , 34 Overexpression of HO-1 can protect steatotic livers from ischemia–reperfusion injury in rats 35 and from chronic ethanol-induced liver injury in mice. 36 Interestingly, HO-1 upregulation reduces hepatic RIP3 expression in mice upon chronic ethanol feeding and protects primary rat hepatocytes from necroptosis induced by co-exposure of ethanol and tumor necrosis factor- α (TNF- α ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, SST and its analogues protect against liver cirrhosis 3 . The SST analogue octreotide alleviates liver cirrhosis by directly inhibiting the synthesis of alpha-smooth muscle actin (α-SMA) and collagens in hepatic stellate cells (HSCs) 4 6 . Furthermore, SST and its analogues reduce splanchnic blood flow and decrease portal vein pressure by inducing the contraction of peripheral vessels, inhibiting the secretion of vasodilatory peptides and the contraction of HSCs 7 – 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Hyperdynamic circulation, which is secondary to the presence of systemic vasodilation, is an important factor in the aggravation and persistence of portal hypertension ( 1 ). Numerous mechanisms are involved in the development of systemic vasodilation, including increased synthesis of nitric oxide (NO) and carbon monoxide (CO) and the activation of K ATP channels in the systemic and splanchnic arterial circulation ( 2 ). Previous studies have demonstrated that the hepatic heme oxygenase-1 (HO-1)/CO system ( 3 ) and NO/nitric oxide synthetase activity are overexpressed in rats with cirrhosis and contribute to portal hypertension ( 4 )…”
Section: Introductionmentioning
confidence: 99%